Peran Kualitas Layanan Dalam Mendorong Kepuasan Pengguna Layanan Kesehatan Puskesmas Kabupaten Sumedang - Alikha Novira; Ramdani Priatna; Hafid Aditya Pradesa (Universitas Katolik Soegijapranata, Semarang, 2020)
This study discusses constructing constructs that form dimensions of the quality of health services and their effects on patient satisfaction. The object of this research was conducted at the Sumedang District Health Service Center. By using quota sample, 100 target sample determined taken from two Health Service Center, Sumedang Selatan Health Center and Kotakaler Health Center. Data analysis techniques using path analysis with the SmartPLS. Further t-test will be conducted to see the significance of the factor weights for each of the constructs in research model. From the results of the analysis and the results of the study, not all of the health service quality models consisting of six dimensions were confirmed well. Two of the six dimensions of service quality, that are Assurance and Empathy, were found to have no significant effects in increasing patient satisfaction at the Sumedang District Health Service Center. Research suggestions include the following: (1) Future studies are expected to use a research model that is longitudinal; (2) Improvement of personal skills, especially in terms of interpersonal skills from all staff, both for medical staff and services.